MEMPROGRAMKAN PENGENALAN BANK SYARIAH DAN LEMBAGA KEUANGAN MIKRO SYARIAH PADA DESA PURASEDA, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Azizah Mursyidah; Ade Yuspardiansyah (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
Islamic banks and Islamic microfinance institutions (LKMS) are very important to pay attentionto. This is because the community needs business capital financing, and with small capital, buthas a large contribution as one of the pillars of the Indonesian economy. On the other hand, theyare vulnerable businesses due to lack of access to capital, small production capacity and relativelynarrow market share. Therefore, a community service program is needed through socializationthat can support economic growth in the region. This community service activity is carried outwith the aim of providing knowledge and information to the public on how to choose the rightfinancing product based on Islamic sharia through collaboration with Islamic financialinstitutions. This community service was carried out in Puraseda Village, Leuwiliang District,Bogor Regency.